2000
DOI: 10.1016/s0378-1097(00)00262-7
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens epsilon toxin causes excessive release of glutamate in the mouse hippocampus

Abstract: The mechanism of neurotoxicity of Clostridium perfringens epsilon toxin to the mouse brain was investigated. Intravenous injection in mice with the toxin caused seizure and excited hippocampal neurons. Microdialysis revealed that epsilon toxin induced excessive glutamate release in the hippocampus. Both the seizure and glutamate release were attenuated by prior injection with riluzole, an inhibitor of presynaptic glutamate release, suggesting that this toxin enhances glutamate efflux, leading to seizure and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…This is an important finding, since in ruminants, renal lesions (i.e., pulpy-kidney disease) are considered to result from autolysis and have not been observed when sheep with enterotoxemia are necropsied immediately after death (22). Miyamoto et al (11) showed that ETX accumulates in the kidneys of mice inoculated with this toxin, which is consistent with the results presented here. Also, the absence of significant histological abnormalities in the intestines of the mice in these experiments is consistent with the findings in natural sheep type D enterotoxemia, in which intestinal changes are not considered to be a feature of the disease (22).…”
Section: Discussionsupporting
confidence: 90%
“…This is an important finding, since in ruminants, renal lesions (i.e., pulpy-kidney disease) are considered to result from autolysis and have not been observed when sheep with enterotoxemia are necropsied immediately after death (22). Miyamoto et al (11) showed that ETX accumulates in the kidneys of mice inoculated with this toxin, which is consistent with the results presented here. Also, the absence of significant histological abnormalities in the intestines of the mice in these experiments is consistent with the findings in natural sheep type D enterotoxemia, in which intestinal changes are not considered to be a feature of the disease (22).…”
Section: Discussionsupporting
confidence: 90%
“…This toxin is produced as a relatively inactive prototoxin with molecular weight of (Miyamoto et al, 2000). It is responsible for the pathogenesis of fatal enterotoxemia in domestic animals.…”
Section: Epsilon-toxin (ε ε ε ε ε)mentioning
confidence: 99%
“…It is responsible for the pathogenesis of fatal enterotoxemia in domestic animals. This toxin exhibits toxicity toward neuronal cells via the glutamatergic system (Miyamoto et al, 1998;Miyamoto et al, 2000) or extravasation in the brain (Finnie, Blumbergs, Manauis, 1999). It has been suggested that is a pore-forming toxin based on the following observations: (i) ε-toxin can form a large complex in the membrane of Madin-Darby canine kidney cells, and permeabilizes them (Petit et al 1997;Nagahama, Ochi, Sakurai, 1998); (ii) the large complex formed by ε-toxin is not dissociated by SDS-treatment, which is a common feature of pore-forming toxins (Petit et al 1997); and (iii) the CD spectrum of ε-toxin shows that it mainly consists of β-sheets (Habeeb, Lee, Atassi, 1973), as observed for pore-forming β-barrel toxins.…”
Section: Epsilon-toxin (ε ε ε ε ε)mentioning
confidence: 99%
“…The toxin has been well defined in terms of the proteolytic activation of epsilon-protoxin (7,10), its pore-forming ability in Madin-Darby canine kidney (MDCK) cell membranes (12,18) and artificial lipid bilayers (19), and its heptamerization in detergent-insoluble glycosphingolipid-enriched microdomains (10,11). However, the pathogenic mechanisms involved in the lethality of epsilontoxin remain largely unknown, except that it exhibits toxicity towards neuronal cells (2,8,9) and blood vessels in the brains of mice and rats (1,3,4). Besides massive necrosis in the brain, pulpy kidneys are noticeable in animals that have died due to enterotoxemia (22).…”
mentioning
confidence: 99%